Bandwidth Enhancement of Trapezoidal Toothed Log-Periodic Antenna Using Slot Configuration - Patre S.R.; Singh S.P. (My University, 2025)
This paper presents a comparative study on bandwidth enhancement techniques of trapezoidal toothed log-periodic antennas (TTLPA). For this study, non-planar and planar configurations of TTLPAs are taken into consideration. For the non-planar category, conventional metal TTLPA and dielectric-loaded TTLPA (DLTTLPA) are used; whereas for the planar category, slot-based TTLPA is utilized. The trapezoidal toothed log-periodic slot antenna (TTLPSA) is highly advantageous over non-planar TTLPA due to its wide bandwidth and low profile. The proposed TTLPSA has compact size and single-sided structure. Due to these properties, the proposed antenna can be easily integrated with other planar circuit components of portable wireless systems. It has overall size of 50.9 × 50.9 × 0.8 mm3 and provides an impedance bandwidth of 8.25:1 (1.6–13.2 GHz) with nearly stable radiation pattern without requirement of balun. The proposed TTLPSA can be a potential candidate for systems requiring broad bandwidth to serve multiple wireless applications as well as for RF energy scavenging. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.